Hubungan Koordinasi Mata dan Tangan dengan Kemampuan Dribbling dan Shooting pada Peserta Ekstrakulikuler Bola Basket di SMP Negeri 2 Singaraja - Teopilus Alexander Tarigan, Samuel; Wahjoedi, Wahjoedi (Dinasti Research, 2025)
This study aims to explore the relationship between eye-hand coordination and dribbling and shooting skills in extracurricular basketball participants at SMP Negeri 2 Singaraja. In sports, especially basketball, good coordination between the eyes and hands is very important to improve playing skills. This study used a correlational method, with the research subjects as many as 28 students consisting of 15 boys and 13 girls. Data were collected through tests and measurements, which were then analyzed using descriptive statistics and hypothesis testing. The results showed a significant relationship between eye-hand coordination and dribbling ability, with a correlation coefficient of 0.896. This indicates that the better the eye-hand coordination, the better the students' dribbling ability. In addition, the relationship between eye-hand coordination and shooting ability was also significant, with a correlation coefficient of 0.873. These findings confirm the importance of programmed and intensive training in developing basic basketball skills, especially in the aspect of coordination. This study contributes to the development of training methods in sports, as well as highlighting the importance of coordination in improving the performance of young athletes. Thus, the results of this study can serve as a reference for coaches and educators in designing effective training programs to improve the ability to play basketball among students.